Graduate Nurses' Perception of the Effect of Simulation on Reducing the Theory-Practice Gap - Joset E. Brown EdD, RN (SAGE Publishing, 2019)
Graduate nurses employed in high-acuity areas can experience a deficit in integrating theoretical concepts in the clinical environment, which is known as the theory-practice gap; this may result in a risk to patient safety with the potential for negative outcomes. Most existing literature address the existence of the theory-practice gap and the benefit of simulation from a faculty perspective. The purpose of this study was to explore the theory-practice gap from the perspectives of graduate nurses based on their experiences and to determine their perceptions of simulation in prelicensure programs as a strategy to address and reduce the gap prior to entry to practice. Cognitive constructivism was the conceptual framework that guided this study. A qualitative phenomenological design was used to explore the lived experiences of 13 graduate nurses with 2 years of less clinical experience by engaging in semistructured interviews. Data analysis revealed that all the graduates experienced the theory-practice gap on their transition to independent clinical practice with variations in degree. In addition, the graduates voiced aspects of their programs which contributed to reducing the challenges experienced during the transition period. The crucial finding was graduate nurses perceived the theory-practice gap could be reduced through the use of high-fidelity simulation utilizing scenario-based learning exercises in prelicensure programs prior to entry to practice.